Nitric Acid Extraction into a TODGA Solvent Modified with 1-Octanol. Issue 2 (23rd February 2019) - Woodhead, David; McLachlan, Fiona; Taylor, Robin; Müllich, Udo; Geist, Andreas; Wilden, Andreas; Modolo, Giuseppe
ABSTRACT: Distribution data for the partition of nitric acid between nitric acid solution and a solvent phase comprising various combinations of TODGA, octanol, and inert kerosene diluent have been generated, covering a range of conditions from 0 to 9 mol/L HNO3 (aq), 0–100% octanol, 0–0.4 mol/L TODGA over a temperature range from 10°C to 50°C. The data have been used to derive a model describing the nitric acid equilibrium between the phases suitable for incorporation in process models of the innovative SANEX process, for example. For the nitric acid/octanol/diluent system, it was found that an accurate prediction of nitric acid distribution could be achieved using a model allowing 1:1, 1:2, and 1:3 nitric acid/octanol adducts. For the nitric acid/TODGA/diluent system, the best models were found to be those allowing 4:1, 3:1, 2:1, 1:1, and 2:2 nitric acid/TODGA adducts. Superimposing the models for nitric acid distribution into the individual extractants and comparing with experimental results for the nitric acid/octanol/TODGA system showed systematic differences indicative of antagonistic and synergistic effects applying in the ranges 0.5–1.5 mol/L HNO3 and >1.5 mol/L HNO3, respectively. These effects were modelled by the inclusion of 0:1:2, 1:1:1, 2:1:3, and 3:1:2 nitric acid/TODGA/octanol adducts. The effect of temperature on nitric acid extraction was well described by an Arrhenius type expression with an activation energy of −25.7 kJ/mol. No diluent dependence was found for nitric acid extraction.